High incidence of germline BRCA mutation in patients with ER low‐positive/PR low‐positive/HER‐2 neu negative tumors. Issue 19 (17th August 2015) - Sanford, Rachel A.; Song, Juhee; Gutierrez‐Barrera, Angelica M.; Profato, Jessica; Woodson, Ashley; Litton, Jennifer Keating; Bedrosian, Isabelle; Albarracin, Constance T.; Valero, Vicente; Arun, Banu
<x xml:space="preserve">Abstract</x> BACKGROUND The 2015 National Comprehensive Cancer Network guidelines recommend that genetic counseling and germline BRCA mutation testing be offered to women under age 60 with triple‐negative breast cancer (TNBC). As a result of the 2010 American Society of Clinical Oncology (ASCO)/College of American Pathologists (CAP) guidelines for breast cancer, patients with breast cancers that are estrogen receptor (ER) or progesterone receptor (PR) low‐positive (1%‐9% on immunohistochemistry) are no longer strictly considered to have TNBC and may not be referred for genetic counseling. However, the incidence of BRCA mutation in patients with hormone receptor (HR) low‐positive breast cancers remains unknown, and current ASCO/CAP guidelines may result in undertesting for BRCA mutations. METHODS A prospectively maintained research database of breast cancer patients evaluated at The University of Texas MD Anderson Cancer Center between 2004 and 2014 was reviewed; 314 patients were identified with HER2/neu–negative breast cancers expressing ER and PR <10% with known BRCA mutation status. RESULTS Three hundred fourteen patients had breast cancers expressing ER and PR <10%; 238 (75.8%) had HR‐negative cancers (<1% ER and PR), and 76 (24.2%) had HR–low‐positive cancers (1%‐9% ER and/or PR). Among patients with HR‐negative tumors, 86 of 238 (36.1%) had a BRCA1/2 mutation, whereas in the HR–low‐positive group, 30 of 76 (39.5%) had a BRCA1/2 mutation. In multivariate analysis, HR status (<1% vs 1%‐9%) was not significantly associated with BRCA1/2 mutations. CONCLUSIONS The incidence of BRCA1/2 mutations is similar in patients with HR–low‐positive breast cancer and patients with HR‐negative breast cancer. Genetic counseling and BRCA testing should be offered to patients under age 60 who have HR–low‐positive breast cancers. Cancer 2015;121:3435–43. © 2015 American Cancer Society.